2018
DOI: 10.1111/age.12740
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis of Ethiopian indigenous chickens from low and high altitudes under heat stress condition reveals differential immune response

Abstract: Ethiopia is an ecologically diverse country; the low altitude regions are hot and humid whereas the high altitude regions are cooler. In this study we analyzed the transcriptome response of high altitude (Addis Ababa) and low altitude (Awash) chickens to heat stress conditions that are prevalent in the low altitude regions. The chickens were free ranged for 20 h in an enclosure in Awash, and then the heart, breast muscle and spleen tissues were collected at 6:00 AM, 12:00 NOON and 6:00 PM to follow a daily cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 84 publications
0
21
0
Order By: Relevance
“…Kenyan IC presents an opportunity to understand the genetic response to HS of hot temperature–adapted chickens. Previous studies on HS adapted and nonadapted chickens revealed the biological mechanisms regulated by HS and identified differential immune response between lowland- and highland-adapted chickens exposed to tropical conditions (Park et al, 2019; Te Pas et al, 2019). In this study, we exposed chickens collected from local farmers in Mombasa, which is located at an elevation of approximately 50 m (lowland) in the Kenyan coast with an average temperature between 22°C and 35°C (Njarui et al, 2016), and from Naivasha, located at an elevation of approximately 1800 m (highland) with an average temperature of 8°C to 26°C (Ouko et al, 2017), to a short-term HS treatment (acute) and a repeated longer-term HS treatment (chronic) and analyzed the transcriptome response of skeletal and cardiac tissues using RNA sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Kenyan IC presents an opportunity to understand the genetic response to HS of hot temperature–adapted chickens. Previous studies on HS adapted and nonadapted chickens revealed the biological mechanisms regulated by HS and identified differential immune response between lowland- and highland-adapted chickens exposed to tropical conditions (Park et al, 2019; Te Pas et al, 2019). In this study, we exposed chickens collected from local farmers in Mombasa, which is located at an elevation of approximately 50 m (lowland) in the Kenyan coast with an average temperature between 22°C and 35°C (Njarui et al, 2016), and from Naivasha, located at an elevation of approximately 1800 m (highland) with an average temperature of 8°C to 26°C (Ouko et al, 2017), to a short-term HS treatment (acute) and a repeated longer-term HS treatment (chronic) and analyzed the transcriptome response of skeletal and cardiac tissues using RNA sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the effects of genetic polymorphisms on the physiological response to hypobaric hypoxia, transcriptional variation from a genome in an individual can provide phenotypic plasticity in response to the extreme environmental conditions, conferring acclimatization to rapid environmental changes. In recent years, transcriptomic profiles in response to hypoxic stress have been investigated in free-ranging or wild endothermic (Pan et al, 2017;Lim et al, 2019;Park et al, 2019;Qi et al, 2019) and model animals (Sharma et al, 2015;Xu et al, 2019). It is well known that hypoxic microenvironments profoundly affect cancer progression in humans (Jing et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, KLHL29 has known functions in the protein degradation process through the ubiquitination pathway, and this gene was also identified as having a heat stress association in catfish (Jin et al, ; Liu et al, ). It is well known that plateau animals mainly have the ability to adapt to high‐altitude anoxic environments, and oxygen thinning can directly lead to increased heart pressure (Park et al, ; Zhu, Guan, & Lei, ). Therefore, KLHL29 is associated with the environmental adaptability of yaks at different altitudes.…”
Section: Resultsmentioning
confidence: 99%